The State Legal Policies on Sharia Application in Changing Pattern of Indonesia’s Islamic Movements - Bani Syarif Maula (Alhurriyah, 2022)
Legal politics are inextricably linked to power politics. Political dynamics in Indonesia are always colored by the dynamics of Islamic politics, as most Indonesians' political aspirations are influenced by Islamic views. This paper examines the evolution of Islamic law in the modern Indonesian democratic system, particularly after the reform era. Indonesia's democratisation gave rise to freedom of expression and opinion. Even today, Islamic conservatism is growing in Indonesia, but this does not mean that radical Islamist groups are gaining strength. Many political organisations, including Islamic parties and other Islamic movements, have liberated themselves and broadened their organisational philosophies in order to address broader issues and concerns. While maintaining their Islamic identity, some Islamic groups are turning towards the secularization of their goals and objectives as a means of adapting to the changing political environment. Political analysts refer to this development as post-Islamism. The current direction of Islamic politics is more accommodating aspects of democracy but still highlights its Islamic sides. This makes the government more accommodative to laws and regulations based on Islamic teachings.Politik hukum tidak lepas dari aspek-aspek politik kekuasaan. Di Indonesia, dinamika politik juga tidak lepas dari politik Islam, karena aspirasi politik sebagian besar masyarakat Indonesia dipengaruhi oleh pandangan Islam. Makalah ini membahas tentang perkembangan hukum Islam dalam sistem demokrasi Indonesia kontemporer, terutama setelah masa reformasi. Demokratisasi Indonesia memunculkan kebebasan berpendapat dan berekspresi. Bahkan saat ini konservatisme Islam di Indonesia semakin meningkat, namun hal itu bukan berarti menguatnya kelompok Islamis radikal. Banyak organisasi politik termasuk partai Islam dan gerakan-gerakan Islam lainnya melakukan pembebasan diri dan melakukan keterbukaan filosofi organisasi mereka untuk mengakomodasi berbagai masalah dan keprihatinan yang lebih luas. Sambil mempertahankan identitas keislamannya, beberapa kelompok Islam beralih ke arah sekularisasi tujuan dan sasaran mereka sebagai sarana untuk beradaptasi dengan lingkungan politik yang berubah. Analis politik menyebut perkembangan ini sebagai post-Islamisme. Arah politik Islam saat ini lebih mengakomodasi aspek-aspek demokrasi namun tetap menonjolkan sisi keislamannya. Hal ini membuat pemerintah lebih bersikap akomodatif terhadap peraturan perundang-undangan yang berlandaskan ajaran Islam.